Evaluating Daylighting Performance and Visual Comfort in Office Spaces with Roller Blinds through Field Measurement and DIALux Evo Simulation - Rusyda, Hana Faza Surya; Anwar, Hendi; Siregar, Fernando Septony; Laksitarani, Niken; Abdulhadi, Reza Hambali William (RUAS, 2026)
Natural daylight plays an essential role in providing visual comfort in office spaces while reducing reliance on artificial lighting, thereby supporting green building principles. This study was conducted at the Jasa Raharja Office in South Jakarta, a building designed in accordance with green building principles and featuring a modern open-plan office layout. The workspace is surrounded by windows that serve as the primary source of daylight, with roller blinds used to regulate daylight penetration. A quantitative approach was employed through field measurements and DIALux Evo simulations to evaluate daylight performance under actual office conditions. Illuminance data were collected at several measurement points and empirically validated against the Indonesian National Standard (SNI). The simulation results indicated an average illuminance of 577 lux with the roller blinds half-open, while field measurements showed an average of 469 lux, yielding an agreement of 81.2%. However, fully exposing the windows without daylight control is not recommended, as it produces an average illuminance of 1,214 lux, which may cause glare and visual fatigue.